Participatory prevalence estimation: A pilot survey in Kenya - Hannah, H.; Grace, Delia; Randolph, Thomas F.; Glanville, William A. de; Fèvre, Eric M. (International Livestock Research Institute, 2012)
There is a need to find locally and globally relevant surveillance tools to measure disease prevalence and inform control programs. Traditional veterinary knowledge has a contested role in surveillance systems. We examined participatory epidemiology (PE) surveys for agreement between community perceptions of prevalence of cattle conditions compared to clinical and laboratory results. Community meetings to understand traditional knowledge of endemic disease were convened in randomly selected communities in Western Province, Kenya. Community perceived prevalence for common cattle diseases and five focus conditions (anemia, helminthosis, fascioliasis, trypanosomiasis and theilieriosis) was determined using PE tools. Within selected communities, all cattle (>1 month old) were clinically examined and blood and stool specimens collected. Definitive diagnosis was made by clinical findings, microscopy and molecular techniques. Agreement was determined for prevalence obtained from community perceptions compared to laboratory and clinical analysis. To assess the ability of individual farmers to identify ill animals and accurately diagnose disease, the perceived health status from animals on randomly selected farms was obtained by owner interview. A clinical examination was then performed with blood and stool specimens analyzed for a battery of other endemic diseases. Agreement between farmer assessment of health status and diagnosis for selected conditions against results from laboratory and clinical examination was determined. This study highlights the accuracy and limitations of traditional knowledge. The usefulness of PE for preliminary prevalence estimation was demonstrated by the ability of non-pastoralist farmers to estimate herd level prevalence and individual animal health status. The study shows that PE can serve to combine local knowledge inquiry with scientific study at a cost lower than laboratory and clinical surveys.